RNA-Seq-Based TCR Profiling Reveals Persistently Increased Intratumoral Clonality in Responders to Anti-PD-1 Therapy - Zhigalova, Ekaterina A.; Izosimova, Anna I.; Yuzhakova, Diana V.; Volchkova, Lilia N.; Shagina, Irina A.; Turchaninova, Maria A.; Serebrovskaya, Ekaterina O.; Zagaynova, Elena V.; Chudakov, Dmitriy M.; Sharonov, George V. (Frontiers in Oncology, 2020)
Substantial effort is being invested in the search for peripheral or intratumoral T cell receptor (TCR) repertoire features that could predict response to immunotherapy. Here we demonstrate the utility of MiXCR software for TCR and immunoglobulin repertoire extraction from RNA-seq data obtained from sorted tumour-infiltrating T and B cells. We use this approach to extract TCR repertoires from RNA-seq data obtained from sorted tumour-infiltrating CD4+ and CD8+ T cells in HKP1 (KrasG12Dp53–/–) syngeneic mouse model of lung cancer after anti-PD-1 treatment. For both subsets, we demonstrate decreased TCR diversity in response to therapy. At later time-point, repertoire diversity is restored in progressing disease, but remains decreased in responders to therapy in both CD4+ and CD8+ subsets. These observations complement previous studies and suggest that stably increased intratumoral CD4+ and CD8+ T cell clonality after anti-PD-1/PD-L1 therapy could serve as a predictor of long-term response.